SUBSTANTIATION OF THE CHOICE OF TREATMENT STRATEGY IN ISOLATED TRAUMATIC INJURY OF THE FRONTAL LOBES OF THE BRAIN - M. M. Smirnova; Yu. A. Shcherbuk (Вестник хирургии имени И.И. Грекова)
An analysis of the results of the treatment of 132 patients with isolated traumatic parenchymatous injury of the frontal lobes of the brain was made. The treatment strategy was determined in consideration of the traumatic substratum volume and a combination of neurologic status and instrumental data. There were unfavorable risk factors to the course of traumatic parenchymatous injury of the frontal lobes of the brain such as low initial GCS score, the progression of neurologic deficiency in the presence of contusion hemorrhagic foci in the frontal lobe with the volume more than 25 cm³, shifting of midline structures on 5 mm and more or signs of deformation of basilar region cisterns and the presence of mass-effect according to the tomographic data. The developed algorithm allowed improving the results of treatment and the quality of life for patients with traumatic parenchymatous injury of the frontal lobes of the brain.